Iman Yang Militan dan Tahan Uji dalam 1 Petrus 1:1-21 - Samiasih, Catur (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2024)
One of the challenges of Christianity today is that the congregation has abandoned its faith. The causal factors include Christianity as a mere religion, Christian descent without a true understanding of faith, and church teachings that do not emphasize understanding of faith in the congregation. The purpose of the study is to explain the understanding of faith that is militant and resistant to testing. If this faith is possessed by Christians, they are able to maintain their faith even though they face many challenges. This study uses a descriptive analysis method from the book of 1 Peter 1:1-21 supported by literature sources related to the verses. From the analysis of the material, it is concluded that militant and resistant faith is faith that is based on love, even though they do not see but believe and love. This level of faith will make Christians survive every challenge.Tantangan Kekristenan masa kini salah satunya adalah jemaat meninggalkan imannya. Faktor penyebabnya antara lain Kristen sekedar agama, Kristen keturunan tanpa pemahaman iman yang benar, dan pengajaran gereja yang tidak menekankan pemahaman iman dalam jemaat. Tujuan penelitian adalah memaparkan pemahaman iman yang militan dan tahan uji. Jika iman ini dimiliki orang Kristen, mereka mampu mempertahankan imannya walaupun menghadapi banyak tantangan. Penelitian ini menggunakan metode kualitatif deskriptif analisis dari kitab 1 Petrus 1:1-22 didukung dengan sumber literatur yang berkaitan dengan nats tersebut. Dari Analisa bahan disimpulkan iman yang militan dan tahan uji adalah iman yang didasarkan kasih, sekalipun tidak melihat namun percaya dan mengasihi. Tingkat iman seperti ini akan menjadikan orang Kristen bertahan dalam setiap tantangan.